Law and norms: empirical evidence - Lane, Tom; Nosenzo, Daniele (University of Nottingham Ningbo China, 2019)
A large theoretical literature argues laws exert a causal effect on norms. This paper is the first to provide a clean empirical test of the proposition. Using an incentivized vignette experiment, we directly measure social norms relating to actions subject to legal thresholds. Results from three samples with around 800 subjects drawn from universities in the UK and China, and the UK general population, show laws often, but not always, influence norms. The strength of the effect varies across different scenarios, with some evidence that it is more powerful when law-breaking is more likely to be intentional and accurately measurable.